Sosialisasi Etika Penggunaan Media Sosial Bagi Siswa SMA YPK Oikumene Manokwari - Yuliana Sangka; Engelberth Worabai; Jennis Tonapa; Yammes J.Batkunde; Zulkarnain; Risma Petrus; Mardewi; Joice Pangulimang; Irmawati Leppang; Sabinus Rainer N. Christi; Sofyan (AMMA : Jurnal Pengabdian Masyarakat, 2025)
In today's technological era, social media has had an impact on everyday life, both positive and negative, and almost all levels of society use social media. Some behaviors that are prone to being done by students, especially high school students, in social media such as cyberbullying, spreading hoaxes, uploading inappropriate content, spreading personal data, hate speech and addiction to social media. It is important to provide an understanding of the ethics of using social media so that there is no behavior that violates norms and can also be avoided from sanctions from the Electronic Information and Transactions Law (ITE). For this reason, participants are equipped with an understanding and skills in utilizing or using social media wisely and responsibly. There are 7 stages that are carried out starting from observation, implementation plan, proposal preparation, activity implementation, evaluation, reporting and publication.